Investigation into the optimal fleet employment strategy with concentration on the supramax bulk carrier east of Suez market - Long, Matthew Jiwei (2014)
In this research we investigate the optimal fleet acquisition strategy for a shipowner who is operating a fleet of 10 Supramax vessels for the period 2006 to 2012.